How to be successful in imitation management? - Gerhard Schewe (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1993)
There is often a clash between the necessity to innovate and the high economic risks involved in the introduction of novelties. The technology-strategies developed in reaction to this situation aim at profiting from the technological leader's or the innovator's experience: the technological follower or imitator enters a market in which the main features have already been developed. An empirical investigation of 66 firms shows that imitation projects are only successful if one succeeds in realizing a high imitation degree and in impeding the market entry of further imitators. Further development or an improvement of the innovation (a low imitation degree) does not affect the imitation success in a positive way. Furthermore, an imitator should be anxious to deteriorate the conditions of market entry for strong late-comers and prevent further imitators from market entry. Further more the results show that successful imitation management has at its disposal technology, intelligence, marketing and production potentials for overcoming existing imitation barriers in which a differential control and coordination of the individual potentials is strictly necessary.
Keywords: 650; Technology management; imitation; technology strategy; imitation success; Innovationsmanagement; Imitationsstrategie; Theorie